EFEKTIVITAS MANAJEMEN SISTEM PENDIDIKAN DAN PELATIHAN PRAJABATAN APARATUR PEMERINTAH GOLONGAN III : Studi Kontribusi Komponen-komponen Proses Belajar Mengajar Terhadap Efektivitas Sistem Pembelajaran dan Dampaknya Terhadap Kinerja Lulusan di Wilayah Provinsi Jawa Barat - Kurniadi, Adang (2010)
Education and training is a medium to improve the performance of civil servants. The management of education and training, especially the one for the pre-service civil servants, has not been well conducted. This is proved by the inappropriate needs analysis of the program, the lack of attention of the administrators on the characteristics of the participants, unselective participant selection, and the lack of relevance between the curriculum and the goals of the program. Those conditions have brought about unexpected results, in terms of the effectiveness of both the input and the impact on the performance of the civil servants (graduates). Based on the aforementioned conditions, there needs to be an evaluation on the administration of the education and training of the pre-service civil servants by focusing attention on the input, process, output, and the impact. This research was conducted on the Agencies, Offices, and Units as the Administrators of Education and Training in the levels of Province, Regency/Cities of West Java as many as 27 units including the Education and Training Agency of West Java Province. The research raised the question of how effective the management of the Pre-Service Education and Training is, both from the aspects of its input and its impact. The input components consist of raw input (participants' characteristics), instrumental input (facilities components), and environmental input (environmental components), their influence on the effectiveness (success) of the learning system and their impact on the performance of the graduates. This research employed quantitative approach. The sample respondents were alumni of Pre-Service Education and Training of Level III Civil Servants years 2006 and 2007 and also their superiors, even the Administrators of Education and Training in the levels of Province and Regency/Cities of West Java. The data collection employed field observation, interview, questionnare distribution (primary), and literary studies (secondary). Data analysis used statistical analysis employing path analysis technique. Results of the descriptive analysis explain that characteristics of the participants, facilities components and environmental components as the teaching-learning process components have not reached their ideal conditions; the same is also true for the effectiveness of the learning system and civil servants performance. The analysis of statistical shows that simultaneously participant characteristics, facilities components, and environmental components have positive and significant influence on the effectiveness of learning system, with total contribution as much as 52% and 48% contribution by other factors; whereas the influence on civil servants performance was as much as 59% and 41% for contribution of other factors. The effectiveness of learning system has positive and significant influence on the enhanced performance of the civil servants, with total contribution as much as 55% and 45% contributed by other factors. Generally, the results show that the management of pre-service education and training system of Level III civil servants has not been effectively conducted so that the program failed to contribute optimally to the improvements on the input, process, output, and outcome need to be immediately conducted by the government through its Education and Training Agencies in the area of West Java Province and the involved institutions by considering the hypothetic model proposed, that is A Model of Value-Based Pre-Service Training and Education of Level III Civil Servant.